2011
DOI: 10.1029/2011tc002908
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of Cenozoic deformation in Asia and the size of Greater India

Abstract: [1] A long-standing problem in the geological evolution of the India-Asia collision zone is how and where convergence between India and Asia was accommodated since collision. Proposed collision ages vary from 65 to 35 Ma, although most data sets are consistent with collision being underway by 50 Ma. Plate reconstructions show that since 50 Ma ∼2400-3200 km (west to east) of India-Asia convergence occurred, much more than the 450-900 km of documented Himalayan shortening. Current models therefore suggest that m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
220
3
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 285 publications
(240 citation statements)
references
References 450 publications
(586 reference statements)
15
220
3
2
Order By: Relevance
“…This is evident from surface expressions of 5 different deformation processes around the globe, such as for example the ongoing crustal deformation processes that formed the Tibetan Plateau due to the continental collision of the Indian and Eurasian Plates (van Hinsbergen et al, 2011) or the rifting of the African Plate induced by its interaction with the Afar plume head (Ebinger and Sleep, 1998). It has been shown that shallow processes influence both the magnitude and orientation of the lithospheric stresses.…”
Section: Introductionmentioning
confidence: 99%
“…This is evident from surface expressions of 5 different deformation processes around the globe, such as for example the ongoing crustal deformation processes that formed the Tibetan Plateau due to the continental collision of the Indian and Eurasian Plates (van Hinsbergen et al, 2011) or the rifting of the African Plate induced by its interaction with the Afar plume head (Ebinger and Sleep, 1998). It has been shown that shallow processes influence both the magnitude and orientation of the lithospheric stresses.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, paleomagnetic data alone places Lhasa anywhere between being south of the equator or in excess of 20 N in pre-collision times. However, equatorial or low latitude positions of Lhasa in the early Eocene would imply extreme post-collisional north-south shortening of the terrane, where only $290 km north-south shortening of the terrane is recorded in the geology from $100 to 20 Ma [van Hinsbergen et al, 2011b]. [25] In the region of Mt Everest, an initial high pressure and temperature metamorphic event at $39 Ma [Cottle et al, 2009] may be indicative of continent-continent collision between Greater India and Lhasa.…”
Section: Insights From Surface Geologymentioning
confidence: 99%
“…This collision, which initiated at 50-52 Ma [Patriat and Achache, 1984;Guillot, 2003;van Hinsbergen et al, 2011] and has led to the creation of world's highest mountain ranges and largest plateaux, is presently ongoing with a convergence velocity of 34 mm/yr near the western syntaxis [Molnar and Stock, 2009;DeMets et al, 2010]. The Pamir, a northwardconvex mountain range, has presumably been moving north relative to the surrounding regions since about 25 Ma [Sobel and Dumitru, 1997], overriding the Tajik-Yarkand Basin [Burtman and Molnar, 1993], which previously connected the Tajik Depression in the west and the Tarim Basin in the east.…”
Section: Tectonic Settingmentioning
confidence: 99%
“…[3] The western Himalaya-Hindu Kush-Pamir system accommodated a similar amount of Cenozoic convergence as the Himalaya-Tibet system, albeit over a much shorter meridional width, resulting in a higher amount of upper plate shortening [van Hinsbergen et al, 2011[van Hinsbergen et al, , deduce 1050 as well as a probably higher amount of crust that vanished into the mantle. Lithospheric deformation is accompanied by vigorous intermediate-depth (up to nearly 300 km depth) earthquake activity [Billington et al, 1977;Pegler and Das, 1998], which is, with the possible exception of Vrancea, Romania [Ismail-Zadeh et al, 2012], globally unique within a continental collision zone far from any active oceanic subduction.…”
Section: Introductionmentioning
confidence: 99%